Analisis Kemampuan Pemecahan Masalah Matematis Pada Materi Bangun Ruang Sisi Datar Berdasarkan Kemampuan Awal Matematika Siswa - Khairatun Nafisah; Muh. Turmuzi; Tabita Wahyu Triutami; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe the mathematical problem-solving ability of the flat-sided geometry based on the initial mathematical abilities of the IX grade students of SMPN 6 Mataram. This type of research is descriptive qualitative. The research subjects of this study consisted of two students in the categories of high, medium, and low mathematics early abilities. Data collection techniques using test and interview methods. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The results showed (1) 2 students with high early mathematical abilities were able to fulfill the three stages of Polya’s indicators, namely understanding the problem, planning problem solving and implementing problem solving plans. So students’ mathematical problem solving abilities are in a good category. (2) 2 students with moderate early mathematics abilities are only able to meet the indicators of understanding the problem. So that students’ mathematical problem solving abilities are in the less category. (3) 2 students with low early mathematics abilities are only able to fulfill the indicators of understanding the problem. So students’ mathematical problem solving abilities are in the very poor category.